Effects of soil compost application on the leaf surface area per running meter of apple (Malus domesticaBorkh.) leaves cultivated in organic and integrated orchard - Szabó, Anita; Csihon, Ádám; Vágó, Imre (Acta Agraria Debreceniensis, 2014)
The effect of different compost doses on the nutrient contents of the soil (in depth of 0–30) were measured in an (organic and integrated) apple orchards. The leaf surface area per running meter shoot for certain apple species (Golden Delicious and Pinova) were determined. The field experiments were conducted in the Research Field of Debrecen-Pallag, University of Debrecen, the analysis of the soil and plant samples took place in the laboratories of the Institute of Agricultural Chemistry and Soil Science. The compost treatments increased the amount of the examined nutrients in the top 30 cm of soil originated from organic and integrated orchard. Changes in rainfall were observed in the trends of the leaf surface area of the two apple varieties. 2010 was rainy and 2012 was drier. The leaf surface area of the Pinova increased better under the precipitation/year effect, than in case of the nutrient supply treatments. The opposite was observed in case of the Golden Delicious.